Tropical frugivorous birds molt and breed in relation to the availability of food resources - Faccio, Maya Sonnenschein; Gabriel, Vagner de Araujo; Pizo, Marco Aurélio [UNESP] (My University, 2018)
Few studies have investigated how the abundance of food resources influences the phenology of the annual cycles of tropical birds. Frugivorous birds are good models for such investigation because the abundance of their main food types, fruits and arthropods, vary independently from each other. We investigated how the consumption and availability of fruits and arthropods are related to breeding and molt cycles of frugivorous birds in a fragmented landscape of the Brazilian Atlantic forest. We recorded the occurrence of brood patches and the molting of flight feathers in mist‐netted birds, from which we also analyzed the contents of fecal samples. Using nonparametric and parametric correlation tests we investigated the relationships among breeding and molt stage with the availability of fruits and arthropods. We found that the availability of fruits and arthropods fluctuates temporally and independently, but both food sources have shortage periods, apparently more pronounced for fruits. During periods when fruit was scarce, birds relied more heavily on arthropods as food. Incubation occurred when fruit availability was high, whereas the molt period that followed was coincident with the availability of arthropods. Although our observational study does not permit definite conclusions regarding the relationship between food availability and the timing of the annual cycle events investigated, it is suggestive that avian breeding and molt cycles coincide with fruit and arthropod availability, respectively. Together with arthropods, fruits are important for nestlings of frugivorous birds, and protein from arthropods may be especially important for the development of new feathers.
Keywords: Arthropod availability; Atlantic forest; Brazil; Breeding cycle; Diet; Fecal samples; Flight feather molt; Frugivorous birds; Fruit availability; Thraupidae; Turdidae; Tyrannidae; Vireonidae